Penilaian Ekonomi Ekosistem Mangrove di Desa Tritih Kulon dan Karangtalun, Kabupaten Cilacap - Wisudyanti, Dewi; Chairummah, Annis; Riviani, Riviani; Ekasanti, Anandita; Listiowati, Emyliana; Nugrayani, Dewi; Pelamonia, Alamanda (MAIYAH, 2024)
Mangrove forests function as a place for the survival of various marine biota such as fish, shrimp, and crabs, especially the mangrove forest area in Tritih Kulon and Karangtalun Villages, Cilacap Regency. Mangrove forests in the area also function as a place for the reproduction of living things that can support the economy of the local community. The purpose of this internship is to determine the economic potential of the mangrove ecosystem and to determine the economic impact of the existence of the mangrove ecosystem on the income of local communities in Tritih Kulon and Karangtalun Villages, Cilacap Regency. This internship was carried out by conducting interviews and distributing questionnaires to obtain data. The results of the internship showed that the economic potential of mangrove forests in the Tritih Kulon area is quite high, namely IDR 330,430,000 and IDR 53,700,000 in Karangtalun Village. The existence of mangrove forests in both locations brings economic value to the local community through tourism activities, fisheries, and home industry production. It is hoped that this research can be a reference in the development of mangrove ecosystems in the future.